PENGARUH LABA, ARUS KAS dan ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR PROSPECTOR dan DEFENDER - Andreas, Lidya; Handoko, Jesica; Harimurti, Yohanes (Widya Mandala Surabaya Catholic University, 2015)
Miles and Snow (1978, in Habbe and Hartono, 2001) classify corporate strategy into four typologies: prospector, defender, analyz-er, and a reactor where prospector and defender was at its extreme. Return the stock as a aims the investor will be different for the company due the defender and prospector how to operate the two companies mutually contradictory. This research aims to test the influence of earnings, cash flow, and economic value added of return stocks as an indicator for investors to predict the return on the company’s stock prospector and defender. This empirical study using consolidated financial report data and information from the Indonesian Capital Market Directory for all manufacturing companies listed on the Indonesian stock exchange. A grouping of companies in the prospector and defender using common factor analysis in accordance with previous research. Earnings, cash flow, and EVA is measured by the weighted average of ordinary shares outstanding. The results showed that only the operating cash flow has the effect on the return on the company’ stock prospector. While in the company of a defender, all variables have no effect on the return of shares. This shows there are still many other variables that can affect the return of shares. In addition the research indicates that the use of the strategy of the prospector and defender influencing variables can be the main indicator in predicting the return of shares.